Prisons and Prisoners : volume 51 - Tonry, Michael; Bucerius, Sandra (Chicago: London: The University of Chicago Press, 2022)
"Volume 51 is a thematic volume on Prisons and Prisoners. Since 1979, the Crime and Justice series has presented a review of the latest international research, providing expertise to enhance the work of sociologists, psychologists, criminal lawyers, justice scholars, and political scientists. The series explores a full range of issues concerning crime, its causes, and its cures. In both the review and the occasional thematic volumes, Crime and Justice offers an interdisciplinary approach to address core issues in criminology. Periodic thematic volumes present research results, reports, and essays on specific topics in criminology. These include Organizing Crime: Mafias, Markets, and Networks (Volume 49); American Sentencing: What Happens and Why? (Volume 48); Reinventing American Criminal Justice (Volume 46); Sentencing Policies and Practices in Western Countries: Comparative and Cross-National Perspectives (Volume 45); Why Crime Rates Fall, and Why They Don't (Volume 43); Crime and Justice in America: 1975-2025 (Volume 42); Prosecutors and Politics: A Comparative Perspective (Volume 41); Crime and Justice in Scandinavia (Volume 40); Crime, Punishment, and Politics in Comparative Perspective (Volume 36); Crime and Justice in the Netherlands (Volume 35); Crime and Punishment in Western Countries, 1980-1999 (Volume 33); Youth Crime and Youth Justice (Volume 31); Prisons (Volume 26); and Youth Violence (Volume 24)"--
Keywords: Prisons; Imprisonment; Prisoners